Incidence of Postpartum Hemorrhage in Induced Versus Normal Labour - Sumaira Jamil, Tayyaba Majeed, Rubina Naureen, Muhammad Abdullah Sheraz, Mirza Zeeshan Sikandar (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Postpartum hemorrhage (PPH), defined as blood loss exceeding 500 mL within 24 hours of childbirth, remains a major cause of maternal morbidity and mortality worldwide. PPH can result in severe complications, including anemia, transfusion requirements, organ dysfunction, and even maternal death. Prompt recognition, effective management, and risk reduction strategies are essential for improving maternal outcomes. Objective: To examine the cause and frequency of Postpartum Hemorrhage (“PPH”) in induced versus normal labour. Methods: This research was conducted in the Obstetrics and Gynecology Department, Unit no.2 at the Central Park Teaching Hospital. The research was conducted on three hundred and ten (310) patients, who were classified into two equal groups for the purposes of fair comparison. Group 1 consisted of one hundred and fifty-five (155) women who were either induced or had a cesarian section whereas Group 2 had one hundred and fifty-five (155) women who underwent a normal labour. The study was conducted in a six (6) month time duration from May 2023 to July 2023, the reason for PPH was observed and recorded in both groups. The patients and the hospital were informed beforehand of the research and written, and at times oral, consents were taken from both for recording the information below. Results: After examining both Group 1 and Group 2, it was observed that induced labour was associated with 5.8% higher risk of PPH as compared to normal labour. It was further observed that frequency of PPH was highest in women induced by oxytocin as compared to women induced by prostaglandin. Practical Implications: It will help in early and prompt management of labour and it also suggest that labour shouldn’t be induced until unless it’s indicated otherwise it can lead to post-partum hemorrhage. Conclusions: The risk of PPH increases with inducing the labour as compared to normal labour which is why a patient should only be induced in case of utmost emergency. Moreover, if such an emergency does arise, one should use prostaglandin as they are safer than oxytocin. Keywords: Postpartum Hemorrhage, Induction, Induced Labour, Labour, Spontaneous Labour, Normal Labour